A Highly Efficient, Linear Ka-Band SiGe HBT Cascode Power Amplifier With a Compact Lumped Element Coupled Line Impedance Inverting Balun - Lee, Hanjung; Han, Insu; Ju, Inchan (IEEE Transactions on Microwave Theory and Techniques, 2024)
This article presents a compact, highly efficient, and linear Ka -band SiGe HBT cascode power amplifier (PA) for emerging low-earth-orbit (LEO) satellite communication (SATCOM). A novel lumped element coupled line impedance inverting balun (ZIB), realized by two broadside coupled lines in a single inductor footprint, is proposed to save chip area while obtaining comparable performance to its distributed counterpart. The systematic design method of the lumped element coupled line ZIB is described in detail. A compact SiGe HBT cascode, with a shared deep trench (DT) layout and its simple model method, is suggested for the PA output stage design. For the first time, a single-ended to differential hybrid PA topology is adopted at Ka -band to broaden BW and reduce insertion loss (IL) in a compact chip size. A prototype Ka -band SiGe HBT cascode PA is implemented in 0.13-μm SiGe HBT BiCMOS. It attains peak output power (POUT) and peak power-added efficiency (PAE) of 22.6 dBm and 40.3% at 28.0 GHz, respectively, demonstrating the highest PAE among any linear Ka -band SiGe HBT PAs and the largest power density among any Si-based Ka -band PAs. The proposed PA can also operate at elevated ambient temperature of 80 °C with negligible degradation in POUTand PAE. It delivers linear POUT(PAVG) of 15.6/13.1 dBm with average PAE (PAEAVG) of 16.3/10.0% at 2.4/3.2-Gbit/s data rate 64/256 QAM 5G NR FR2 CP modulated signal. This ultracompact Ka -band SiGe HBT PA is suitable for a low-cost, highly integrated transmit beamformer ICs (BFICs) for emerging LEO SATCOM phased array.
Keywords: Balun; Baluns; BiCMOS; Cascode; Coupled-lines; Earth orbits; Impedance; Inverting; Ka band; Low earth orbit; Low earth orbit satellites; Lumped element; Millimeter-wave; Phased-arrays; Power amplifier; Satellite communication; Satellite communications; Transformer; Transmitter (TX); Balun; BiCMOS; cascode; coupled line; HBT; inverting; Ka-band; low earth orbit (LEO); lumped element; millimeter-wave (mmWave); phased array; power amplifier (PA); satellite communication (SATCOM); SiGe; transformer; transmitter (TX)